Reduced folate carrier 1 (RFC1) gene polymorphisms among acute lymphoblastic leukemia patients - Mashaer Taha Edris; Maye Mohammad Merghani; Shaza Salih Gafar; Ahmed Mohamed Asmeli; Elrashed B. Yasin; Raed Alserihi; Haitham M.H. Qutob; Aymen Yasin; Elshazali Ali (Journal of Biological Research)
Reduced Folate Carrier1 (RFC1) gene's metabolism is crucial for DNA synthesis, epigenetic mechanisms, and cellular methylation events. Nonetheless, RFC1 polymorphisms have drawn a lot of interest in current medical genetics studies. The objectives of the study were to ascertain the relationship between the risk of acute lymphoblastic leukemia in Sudanese patients and the genetic variant of RFC1 (G 80A). Using Real-Time Polymerase Chain Reaction (RT-PCR) method, 150 Acute Lymphoblastic Leukemia (ALL) patients and 150 healthy control volunteers had their DNA collected and examined for the case-control study. Version 25 of the Statistical Package for Social Science (SPSS) software was used to analyze the data. There was no discernible difference in the age or gender of the patients compared to the controls. According to Flow cytometry data, T-ALL accounts for 31 (21%) and B cell type accounts for 119 (79%). According to this study, there is a statistically significant correlation between the mean blast (p=0.050) and the mean total white blood cell count (p=0.000) in T-ALL cases. The genotype frequency of RFC1 (G80A) was found to be GG 39 (26.0%), GA 41 (27.3%), and 70 (46.7%) for AA in the cases, while GG 41 (27.3%), GA 28 (18.7%), and AA 81 (54.0%) in the control group. While the homozygous genotypes AA and GG were more common in the control group, the heterozygous genotype GA was more common in the patient group. On the other hand, the genotype distribution among the research groups was not statistically significant with odds ratio: 0.745 (0.473-1.174), p=0.192. In conclusion,  RFC1 (G80A) polymorphism was not found to be associated with an increased risk of ALL, according to the findings of this investigation.